a EXPERIMENTAL STUDY: SIGNATURE COCKTAIL WITH HOMEMADE MATAH CORDIAL: - - iskandar, ridwan; Daniati, Hana; Maulana Yusuf , Muhamad (JURNAL GASTRONOMI INDONESIA, 2025)
The creation of mixing drinks or better known as mixology continues to develop with various innovations in techniques, ingredients, and presentation concepts. The current phenomenon is that several bars in cocktails and mocktails use local ingredients and homemade ingredients. This is the author's attraction in conducting research by creating a signature cocktail based on homemade Matah Cordial. This aims to analyze its sensory characteristics, as well as measure the level of consumer acceptance of this product. It is expected to produce products that can be applied in the hospitality industry, bars or cafes. With an experimental-based approach, this study will explore various cocktail formulations that use homemade Matah Cordial, test sensory aspects, and assess consumer preferences through hedonic tests.